Substrates for rapid propagation of table cassava - Alves, Aaron de Sousa; Lopes, Khayran; Araújo, Whéllyson Pereira; Melo Júnior, Arsenio Pessoa de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Present in all regions, cassava is of fundamental importance in human and animal nutrition, either as a raw material for obtaining industrial products and for generating employment and income in the field. In the midst of the relevance of this culture to the current national economic scenario, the objective of this study was to evaluate the effects of different substrate compositions on the development of vegetative structures of cassava of the table type by adapting the technique of rapid propagation, as an alternative to offering better quality seedlings to traditional communities in the semi-arid region of Piauí. The experiment was developed in a protected environment at the Federal Institute of Piauí - IFPI, Campus Oeiras. Obeying the randomized block design, 12 substrate compositions formulated from the mixture of washed sand, soil and bovine manure were tested. The Soil + washed sand + bovine manure (1:1:2) and washed sand + bovine manure (1: 2) substrates are efficient for the vegetative development of table-type cassava sprouts, allowing better seedling production quality for establishment in the field and are recommended for the production of crop seedlings in the rapid propagation process.